Familial case of Gorlin-Goltz syndrome associated with craniosynostosis - Mohan, Ravi Prakash Sasankoti; Gupta, Akanksha; Kamarthi, Nagaraju (Journal of Oral Diagnosis, 2017)
Gorlin-Goltz Syndrome is inherited as an autosomal dominant disorder and occurs due to mutations in the PTCH1 (Patched 1) gene. It is characterized by multiple keratocystic odontogenic tumors, multiple basal cell carcinomas, skeletal, ophthalmic, neurological ab- normalities and facial dysmorphism. Craniosynostosis is the premature fusion of calvarial bones leading to an abnormal head shape. In addition to all the classical features, presence of craniosynostosis in one of our cases was an interesting finding which has never been reported previously in Gorlin-Goltz syndrome. Giant congenital melanocytic nevus was also present making the case more unique.